2010
DOI: 10.1080/09540121.2010.487089
|View full text |Cite
|
Sign up to set email alerts
|

Demographic factors and sexist beliefs as predictors of condom use among Latinos in the USA

Abstract: Based on a survey conducted among 198 Latinos in Central Illinois, USA, this study shows that income, education, and language skills were important predictors of condom use. In addition, hostile and benevolent sexist ideas had a differing impact on condom use. Hostile sexist ideas, such as the belief that women try to control men, increased condom use with both main and occasional partners. Benevolent sexism, for example, the idea that women should be cherished and protected, was negatively and significantly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Similar to Albarracin and Plambeck (2010) and Vandello et al (2009), our findings suggest that it is important to study ambivalent sexism among Hispanics. Although their studies focused on how sexism was linked to specific harmful behaviors, such as not using condoms as well as indirect violence against women, our study focused on attitudes embedded in relational scripts.…”
Section: Ambivalent Sexism and Latino Cultural And Stereotypical Depisupporting
confidence: 89%
“…Similar to Albarracin and Plambeck (2010) and Vandello et al (2009), our findings suggest that it is important to study ambivalent sexism among Hispanics. Although their studies focused on how sexism was linked to specific harmful behaviors, such as not using condoms as well as indirect violence against women, our study focused on attitudes embedded in relational scripts.…”
Section: Ambivalent Sexism and Latino Cultural And Stereotypical Depisupporting
confidence: 89%
“…Abounding literature identified gender factors (including gender, sexism, and gender stereotypes) as significant drivers of HIV infection in HIV/AIDS prevalent areas [13,25,26]. Gender, as a cultural symbolization of sexual difference has had a profound mark on human existence and has been linked with increased vulnerability to HIV infection [1,[27][28][29]. Specifically, gender inequality has been implicated for increased risk and vulnerability to HIV infection as well as sexual risk behaviour [26][27][28][29][30][31].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Gender, as a cultural symbolization of sexual difference has had a profound mark on human existence and has been linked with increased vulnerability to HIV infection [1,[27][28][29]. Specifically, gender inequality has been implicated for increased risk and vulnerability to HIV infection as well as sexual risk behaviour [26][27][28][29][30][31]. Researchers noted that gender inequality is often borne out of gender stereotypes and sexist orientation [32,33].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Thus, although engaging in intercourse out of a desire to promote a relationship may very well lead to positive inter-and intra-personal outcomes; the current findings suggest that these benefits may come with a cost (i.e., less condom use). Coupled with Albarracin and Plambeck's (2010) work showing that men with benevolent sexist attitudes are less likely to report condom use with their primary partner (Albarracin and Plambeck speculate this is because benevolently sexist men are more trusting of women and perceive them to be "pure" and STI-free), the present results are particularly noteworthy-and troubling-for women in relationships with such men: they (and their partners) may be doubly at risk of engaging in unprotected sex because the sexist attitudes and behaviors their partners bring to the bedside may curtail both parties' safer sex practices. The current study indicated that personal, sexual behaviors may be shaped by larger social forces (such as perceived sexism), and hence, underscores the importance of contextualizing condom use within the broader social landscape and not taking an overly individualistic approach to understanding risky sexual behavior.…”
Section: Discussionmentioning
confidence: 98%